Investigating the role of Cut Like Homeobox 1 CUX1 in colorectal cancer progression - Rusnita, Dewi (2024)
CUX1, also known as Cut-like homeobox 1, is a gene that has been identified as a transcriptional factor capable of regulating the expression of other genes involved in various cellular processes. It has emerged as a gene of interest due to its potential role in the progression of colorectal cancer (CRC), as indicated by analysis of cases from The Cancer Genome Atlas (TCGA). However, the precise function of CUX1 in colorectal cancer progression is not yet fully understood, and there is limited research examining its expression and role in this type of cancer, particularly with regards to its impact on cancer progression. Therefore, this study aimed to investigate the role of CUX1 in colorectal cancer progression using immunohistochemistry to assess CUX1 staining, in vitro functional studies, and RNA sequencing of CRC cell lines.